2017
DOI: 10.3892/etm.2017.4625
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Taohongsiwu decoction on the expression of α-SMA and TGF-β1 mRNA in the liver tissues of a rat model of hepatic cirrhosis

Abstract: The present study aimed to explore the treatment effects of Taohongsiwu decoction on the liver fibrosis in a rat model, as few prior studies have investigated the anti-fibrotic effects of Taohongsiwu decoction. High-performance liquid chromatography was used to measure the concentration of ferulic acid and hydrosafflower flavin A in the decoction. Male Sprague-Dawley rats were randomly divided into control, model, colchicine (positive group), Taohongsiwu-high, Taohongsiwu-moderate and Taohongsiwu-low groups; 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
2
0
1
Order By: Relevance
“…It is a tissue repair process observed in various chronic liver injuries, and can result in cirrhosis in severe cases (49,50). Increased α-SMA and type I collagen expression levels are important markers of liver fibrosis (51), and according to the results of the present study, miR-148a-3p treatment markedly inhibited α-SMA and type I collagen expression levels in the ALF rats, indicating that miR-148a-3p can improve liver fibrosis caused by alcohol.…”
Section: Discussionsupporting
confidence: 73%
“…It is a tissue repair process observed in various chronic liver injuries, and can result in cirrhosis in severe cases (49,50). Increased α-SMA and type I collagen expression levels are important markers of liver fibrosis (51), and according to the results of the present study, miR-148a-3p treatment markedly inhibited α-SMA and type I collagen expression levels in the ALF rats, indicating that miR-148a-3p can improve liver fibrosis caused by alcohol.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, in the model of acute TAA-induced liver injury, the activation of stellate liver cells was also described as a critical event by us and others [ 35 , 36 ]. Activated hepatic stellate cells are capable of ECM overproduction, including collagen I and III, hyaluronic acid and laminin, decreasing the collagenase activity and collagen degradation [ 37 , 38 ]. Expression of α-SMA is a representative sign of activated stellate liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies reported, increased α-SMA and collagen I expression levels are important markers of liver fibrosis [20]. TGF-β1, as a major fibrogenic factor, could promote the epithelial-mesenchymal transition (EMT) and lung fibroblast-to-myofibroblast transdifferentiation [21].…”
Section: Discussionmentioning
confidence: 93%